The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1103/physreva.79.042319
|View full text |Cite
|
Sign up to set email alerts
|

Dzyaloshinskii-Moriya interaction and anisotropy effects on the entanglement of the Heisenberg model

Abstract: In this paper the the effect of Dzyaloshinskii-Moriya interaction and anisotropy on the Entanglement of Heisenberg model has been studied. While the anisotropy suppress the entanglement due to favoring of the alignment of spins, the DM interaction restore the spoiled entanglement via the introduction of the quantum fluctuations. Thermodynamic limit of the model and emerging of nonanalytic behavior of the entanglement have also been probed. The singularities of the entanglement correspond to the critical bounda… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
105
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(113 citation statements)
references
References 38 publications
6
105
0
Order By: Relevance
“…To slightly generalize it, let us add a Dzyaloshinskii-Moriya (DM) interaction 20 and on every link we consider the operators,…”
Section: Limiting Cases: Xy and Xxz Chainsmentioning
confidence: 99%
See 1 more Smart Citation
“…To slightly generalize it, let us add a Dzyaloshinskii-Moriya (DM) interaction 20 and on every link we consider the operators,…”
Section: Limiting Cases: Xy and Xxz Chainsmentioning
confidence: 99%
“…The field theory value of ∆ c is πJ/2 while the exact solution gives ∆ c = J 13 . The XXZ limit that would correspond to massless Thirring model has been analyzed from spin systems and entanglement points of view 20,22 where the critical value is obtained to be ∆ c = J. In the λ = 0 situation a Dzyaloshinskii-Moriya interaction of strength D can be added to the above XXZ form which results in a gapless line separating the spin-fluid phase from ferromagnetic and/or anti-ferromagnetic Ising phases depending on the sign of ∆ 20 .…”
Section: Introductionmentioning
confidence: 99%
“…The pairwise entanglement of the system is also discussed by means of quantum renormalization group (QRG) method [16,17]. Very recently, the spin−1/2 Ising and Heisenberg models are studied by using the same method by a group of Iran and found that the systems exist QPT [18][19][20][21]. It is also shown that the nonanalytic behavior of the entanglement and the scaling behaviors closing to the quantum critical point are obtained.…”
Section: Introductionmentioning
confidence: 99%
“…The Dzyaloshinsky-Moriya exchange interaction describes superexchange between the interacting spins, and is known to generate many dramatical features [18][19][20][21][22]. It is found that DM interaction can excite entanglement and teleportation fidelity.…”
Section: Introductionmentioning
confidence: 99%